Investigating the Influence of Shareholder Rights Mechanisms on the Perceived Performance of Listed Firms in Nigeria - Nuhu, Mohammed; Rogo, Halilu Bello; Danladi, Mohammed Umar (2017)
The current debate of the issues of shareholder rights to firm performance have grown a topic of research both in the developed and emerging economy.There is serious concern regarding the effectiveness of the board of directors’ transparency and accountability, company image and the rights of the shareholders in recent times.This paper attempts to investigate the influence of shareholders rights mechanisms to perceived performance of listed firms in Nigeria. The underpinning theory of the paper is rooted in agency theory and supported by stewardship theory to increase the understanding of the influence of the board of directors’ transparency and accountability, company image and the shareholder rights to the perceived firm performance.The questionnaire was used as an instrument for data collection from the sampled respondents. Administered to the respondents.247 copies of the questionnaire were administered with 117 duly completed and returned.Empirical findings showed that board of directors’ transparency and accountability and shareholder right were positively associated with perceived firm performance.While company image did not show any significant link to perceived firm performance. The findings contribute theoretically to the knowledge of corporate governance. Based on the knowledge of this study, this is the first study that adopts the use of primary data to investigate the influence of shareholders’ rights mechanisms on the perceived performance of listed firms in Nigeria. The findings provide policymakers, stakeholders, and government with a better picture of the transparency and accountability and the right of the shareholder.